Activity enhancement of CotA laccase by hydrophilic engineering, histidine tag optimization and static culture. Issue 1 (28th December 2017) - Li, Lei; Xie, Tian; Liu, Zhongchuan; Feng, Hong; Wang, Ganggang
Abstract: CotA protein from Bacillus subtilis is of laccase activity. The solubility of recombinant CotA is low, which hinders its application. In this study, histidine tag position optimization and hydrophilic engineering were applied to increase the yield and activity of CotA protein. The results showed that the protein yield of CotA with his tag at C-terminal (CH6-CotA) was four times of that of NH6-CotA (His tag at N-terminal). Then, 23 single mutants were constructed by substitutions of hydrophobic residues with hydrophilic amino acids. Among them, the protein yield of the mutant F207Y was increased by 30%; the catalytic activity ( kcat / Km ) of V403T and P455S was two and three times higher than that of CH6-CotA, respectively. Finally, triple mutant F2071Y/V403T/P455S with C-terminal his-tag (CH6-TSY) was constructed. When the proteins were expressed in microanaerobic condition, the activities of mutants CH6-P455S and CH6-TSY were enhanced about 48- and 42-folds compared to that of NH6-CotA in non-static culture.